Ending the siege? David Ervine and the struggle for progressive Loyalism. Issue 2 (3rd April 2018) - Parr, Connal
ABSTRACT: Drawn from newspapers and interviews with political colleagues, relatives, and conflict intermediaries, this article concerns the late Loyalist political leader David Ervine – an ideal vector through which to explore the recent history and struggle for progressive Loyalism within Protestant working-class East Belfast. It outlines the vital influence of his father, as well as Ervine's ability to find mentorship in others. It covers his imprisonment in Long Kesh, early political awakening, and later success as a representative of the Progressive Unionist Party. It argues that Ervine's chief political opposition eventually came from establishment and hard-line Unionism, and that his primary achievement was to articulate Ulster Loyalist positions and demands against this culture. Ervine's duality as a political representative who was close to the militarism of his former career is shown as being central to his political persona. Ervine's premature passing is shown to be connected to the pressures arising from pursuing progressive policies and stances from a Loyalist background, frequently under fire from other Unionists.